Urgensi Kompetensi Pedagogi Guru sebagai influencer Pendidikan - I Putu Suardipa (Purwadita : Jurnal Agama dan Budaya, 2020)
The accentuation of education is being shaken by various progesifitas changes with the demands of innovation and community needs, and is challenged to be able to respond to local problems and rapidly global change. The changes and problems such as the free market, the development of science, technology and information, art, culture, are very powerful.  Thus, with the development must be coupled with the development in the educational world, ranging from the quality of education to the quality of teachers, students, curriculum, and infrastructure quality, so that the human resources will be based Also. This has been a separate urgency scale on educational jargon. Teachers must have the ability to manage learning, the ability to provide good examples, the ability to be PROFESIOANL teachers, and the ability to communicate and interact. These abilities have been reflected in the four competencies of teachers namely, pedagogic, personality, professional, and social that have become the minimum standard that a prospective educator must have as an influencer Keyword: competence of teacher pedagogy, education.